(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article substantiates the need to develop a marketing strategy in order to increase the level of competitiveness of the organization, considers the marketing management system, its dependence on constant changes in the economic environment. The degree of significance of competitive advantages in the modern market is determined.